Effects of Bifidobacterium Quadruple Viable Tablets Combined with Immune-Enhancing Enteral Nutritional Adjuvant Therapy on Intestinal Flora, Intestinal Mucosal Barrier and Immune Function in Elderly Patients with Hepatitis B Cirrhosis - Xing, Mengmeng; Xiao, Chuanshun; Wang, Xiangzhong Liu Yongmei (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives Hepatitis B cirrhosis is a serious condition caused by the hepatitis B virus, leading to liver fibrosis and vascular proliferation. Current clinical treatments still have limitations, prompting interest in microecological agents and immune-enhancing nutrition. Recent studies indicated the crucial role of intestinal flora imbalance in cirrhosis development, which might be modulated by the “liver-gut” axis. Therefore, this study aimed to investigate the impact of integrating microecological agents and immune-enhanced enteral nutritional support with antiviral therapy on the intestinal flora, mucosal barrier, and immune function in elderly patients with hepatitis B cirrhosis. Materials and Methods Eighty cases of elderly patients diagnosed with hepatitis B cirrhosis in our hospital from January 2020 to December 2022 were included in this retrospective study as study subjects. Both groups received oral tenofovir disoproxil fumarate tablets. The control group underwent basic treatments, including hepatoprotection and a specific diet. The observation group received Bifidobacterium bifidum tetragonum in conjunction with immune-enhanced enteral nutritional support. Nutritional status, gut microbiota, cellular immune status, and intestinal mucosal barrier function were compared before and after intervention in both groups. Results There were no significant differences in baseline characteristics between the groups. After 30 days of treatment, the observation group exhibited significantly increased Enterococci, Enterobacteriaceae, Bifidobacteria, and Lactobacillus abundance compared to pre-treatment and the control group. Inflammatory response indicators and CD8+ expression in the observation group at 7 days postoperatively were markedly lower than control, while CD4+ and CD4+/CD8+ were significantly higher. Nutritional indicators and intestinal mucosal barrier function were also superior in the experimental group after 30 days. Conclusion In conclusion, microecological agents combined with immune-enhancing enteral nutrition support effectively enhance the intestinal mucosal barrier, immune function, and nutritional status in elderly patients with hepatitis B cirrhosis.
Keywords: Microecological agents; Enteral nutrition; Chronic hepatitis B; Liver cirrhosis